Bat overpasses: An insufficient solution to restore habitat connectivity across roads. Issue 3 (20th November 2018) - Claireau, Fabien; Bas, Yves; Puechmaille, Sébastien J.; Julien, Jean‐François; Allegrini, Benjamin; Kerbiriou, Christian
Abstract: Roads have many negative effects on wildlife, including their role in habitat fragmentation. Habitat fragmentation affects bats during their daily movements between roosts and foraging areas. As bats are protected in Europe, developers must implement specific mitigation measures that are hierarchically structured to achieve a null net impact. However, very few specific mitigation measures have been undertaken specifically for bats. Bat overpasses (e.g. gantries) are among proposed improvements intended to reduce the impact of roads, but they have rarely been tested. The effectiveness of overpasses in facilitating safe road crossing of bats is critical for justifying the implementation of this mitigation measure. We therefore assessed whether bat overpasses are effectively used by bats. We studied three bat overpasses with different designs in France. We developed an innovative method to characterize bat crossings using acoustic flight path reconstruction (AFPR). We used six pairs of stereo acoustic recorders in different habitat types that were located on both sides of the road, and operated simultaneously throughout the night. Recording data contained 57, 941 bat passes and 284 bat crossings from six species of bats at the three study sites. Our results suggest that crossings are more numerous if an overpass is located where bat commuting routes have been identified by environmental impact assessment. However, we found that the proportion of bat crossings along the commuting route was the same with or without an overpass; thus highlighting that bat overpasses do not fully restore habitat connectivity. Synthesis and applications . Our study demonstrates that acoustic flight path reconstruction (AFPR) is a useful approach to obtain information on bat flight behaviour. We also emphasize the importance of field testing the effectiveness of mitigation measures, such as those intended to offset the impact of roads on biodiversity, and highlight that such measures should not be implemented based on their theoretical effectiveness alone. Abstract : Our study demonstrates that acoustic flight path reconstruction (AFPR) is a useful approach to obtain information on bat flight behaviour. We also emphasize the importance of field testing the effectiveness of mitigation measures, such as those intended to offset the impact of roads on biodiversity, and highlight that such measures should not be implemented based on their theoretical effectiveness alone.